HADITS TENTANG ANJURAN BERBAKTI KEPADA KEDUA ORANG TUA - Marlina Marlina (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Father and mother, father and mother, abi and umi, papa and mama are parents who are very instrumental and play a role in us. In their hands, from before birth until now, we are always cared for, cared for, protected and made happy. Without expecting anything in return from us, they sincerely and willingly raise us, educate us to become useful people for the religion, nation and state. They always pray for us. They work hard to be able to provide us with food and necessities. No complaints. They do it all happily. If we reflect on the struggle of our parents in raising us, we should do good and be filial towards our parents or in Islam it is often called birrul walidain. They deserve kindness and respect from their children.